Effectiveness and safety of esketamine in laparoscopic surgery patients: a systematic review and meta-analysis of randomized controlled trials - Wang, Shuhui; Hao, Wei; Fan, Hao; Wu, Jiasheng; Wu, Lifang (Frontiers in Pharmacology, 2025)
ObjectivesLaparoscopic surgery is commonly performed, with perioperative treatments aimed at minimizing its impact on patients. Esketamine, known for its antidepressant mechanism, has gained attention as an anesthetic. This review evaluates its effectiveness and safety in laparoscopic surgery patients, since existing trials report conflicting results.Patients and methodsA systematic search across eight databases identified RCTs (Randomized Controlled Trials) on esketamine’s effects in laparoscopic surgery patients. Outcomes assessed included VAS (Visual Analog Scale), AIS (Athens Insomnia Scale), NRS (Numeric Rating Scale), QoR-15 (Postoperative Quality of Recovery), remifentanil consumption, ICFS-10 (Inpatient Cognitive Function Scale) scores, and plasma BDNF (brain-derived neurotrophic factor) concentrations. The study is registered in PROSPERO (CRD42025630085).ResultsFifteen studies involving 1,553 participants were included. Esketamine reduced postoperative VAS (SMD: −0.47; 95% CI [-0.89, −0.05]; P = 0.027) and NRS scores (SMD: −0.36; 95% CI [-0.70, −0.01]; P = 0.042). It also decreased AIS scores on the first (SMD: −0.55; 95% CI [-1.03, −0.07]; P = 0.026) and third days (SMD: −0.85; 95% CI [−1.42, −0.29]; P = 0.003), and ICFS-10 scores (first: SMD: −0.55; third: SMD: −0.62). Additionally, esketamine lowered remifentanil consumption (SMD: −0.58; P = 0.003) and infusion rate (SMD: −0.40; P = 0.001), while increasing plasma BDNF concentrations (SMD: 1.19; P = 0.044). Sensitivity analysis confirmed the stability of these results.ConclusionEsketamine alleviates postoperative pain, reduces remifentanil and opioid consumption, improves sleep quality and recovery, mitigates postoperative fatigue, and increases plasma BDNF concentrations in laparoscopic surgery patients. Nevertheless, this meta-analysis still has certain limitations, most notably the high heterogeneity of the studies incorporated and the limited geographical coverage of the research sites. Further studies are needed to confirm these findings and support its use in improving perioperative outcomes.